Brazil against development: an Amendment Constitucional 95/2016 analysis in Amartya sen’s thoughts - Teixeira , Carla Noura; Mendes, Andréa Dyane Nogueira (Seven Editora, 2023)
The general objective of this study is to analyze the Constitutional Amendment 95 of 2016 in the light of the work “Desenvolvimento como Liberdade” by the author Amartya Sen, in order to arrive at the hypothesis that Brazil is on the opposite path to development seen from a different perspective. much broader than just raising incomes and capital, seen beyond economic development. DOI: https://doi.org/10.56238/methofocusinterv1-045